PENINGKATAN KEMAMPUAN APRESIASI DRAMA DENGAN PENDEKATAN RESPON ANALISIS PADA MAHASISWA PRODI BAHASA DAN SASTRA INDONESIA - Emi Agustina; Catur Wulandari (Wacana: Jurnal Penelitian Bahasa, Sastra dan Pengajaran, 2016)
Literary teaching given previously was only theories and lack of involving students actively. Besides the limited material resources available at school and library, there are only textbooks. The application of analysis response approach can increase the literary teaching at schools and library. The objective of the research was to try to apply response analysis approach in either teaching literature or in dramas. It was hoped that this research can solve teachers’ problem in teaching literature. This research employed classroom action research procedures which covered four step: planning, action, observation and reflection. The results shows that application of the analysis response approach in drama subject can increase the ability of the third semester students of the Indonesian Language and Literary Education Study Program and it is able to raise students’ involvement in group work discussions.